Dimensions and Correlates of Agripreneurial Competency - Panigrahi, Sushree Purabi; Ghadei, Kalyan; Maji, Saikat; Nikhil, J; Gupta, Rohan Prasad; Singh, Jahnavi (Indian Journal of Extension Education, 2025)
Competency implies that a person with competency possesses the skills and abilities necessary to compete effectively with others. In the present study competency of the agripreneuers measured using the suitable scale in KBK (Kalahandi, Balangir, Koraput, Malkanagiri, Nuapada, Balangir, Sonepur and Raygada) districts of Odisha. State and districts were selected purposively, whereas, respondents were selected randomly. Descriptive research design was followed. Data were collected from the respondents in 2024. A total 17 statements were included under five different dimensions i.e. opportunistic competency, organising competency, strategic competency, commitment competency and personal competency. It was observed that majority of the respondents (63.60%) possessed medium level of competency. It was identified that age, education, annul income and agripreneurial experience were positively associated with their competency level. Further it was noted that, two independent variables age and experience together contributed 70.4 per cent of variance in respondent’s competency level.
Keywords: Agripreneur; Competency; , KBK districts; Opportunistic competency; Organising competency; Strategic competency; Commitment competency; Personal competency